Versatile Light‐Mediated Synthesis of Degradable Bottlebrush Polymers Using α‐Lipoic Acid - Lee, Dongjoo; Wang, Hanqing; Jiang, Shu‐Yan; Verduzco, Rafael (Angewandte Chemie International Edition, 2024)
Bottlebrush polymers have a variety of useful properties including a high entanglement molecular weight, low Young's modulus, and rapid kinetics for self‐assembly. However, the translation of bottlebrushes to real‐world applications is limited by complex, multi‐step synthetic pathways and polymerization reactions that rely on air‐sensitive catalysts. Additionally, most bottlebrushes are non‐degradable. Herein, we report an inexpensive, versatile, and simple approach to synthesize degradable bottlebrush polymers under mild reaction conditions. Our approach relies on the “grafting‐through” polymerization of α‐lipoic acid (LA)‐functionalized macromonomers. These macromonomers can be polymerized under mild, catalyst‐free conditions, and due to reversibility of the disulfide bond in LA, the resulting bottlebrush polymers can be depolymerized by cleaving disulfide backbone bonds. Bottlebrushes with various side‐chain chemistries can be prepared through the atom transfer radical polymerization (ATRP) of LA‐functionalized macromonomers, and the backbone length is governed by the macromonomer molecular weight and solvent polarity. We also demonstrate that LA‐functionalized macromonomers can be copolymerized with acrylates to form degradable bottlebrush networks. This work demonstrates the preparation of degradable bottlebrush polymers with a variety of side‐chain chemistries and provides insight into the light‐mediated grafting‐through polymerization of dithiolane‐functionalized macromonomers. Two‐step approach to bottlebrush synthesis using α‐lipoic acid (LA) enables control over side‐chain chemistry and catalyst‐free synthesis of degradable bottlebrush polymers.